The Status and Challenges of Entrepreneurship Education in Vocational Higher Education Institutions in Indonesia - Usman, Ahmadi; Hamid, Abdul (Jurnal Kewirausahaan dan Bisnis, 2022)
Vocational higher education is one of the types of Indonesian higher education. In practice, entrepreneurship has been considered the most important subject that should be taught in vocational higher institutions. Numerous studies have been conducted by discussing the topic of vocational education and entrepreneurship in Indonesia. However, limited studies have been conducted on implementing entrepreneurship education at the Indonesian vocational higher education level. This study aims to explain the status and challenges of entrepreneurship education in Indonesian vocational higher education institutions. The method used in the study was based on a descriptive qualitative method focusing on a contextual review of the literature. The review is enhanced by collecting data from articles, books, reports, and vocational higher education intuitions' websites. This study found that entrepreneurship education has been implemented in vocational higher education institutions, although some aspects still need improvements. Further, the development of entrepreneurship education in vocational higher education institutions in Indonesia is confronted by internal and external challenges. Lastly, the study's findings have significant implications for researchers, policymakers, and entrepreneurship educators.Keywords: challenges; entrepreneurship education; institutions; status; vocational higher education